Centres and peripheries in banking the historical development of financial markets - Cottrell, P. L. 1944-; Lange, Even; Olsson, Ulf; Fraser, Iain L.; Fraser, Monika Pohle (Studies in banking history, 2007)
Based on papers given to the European Association for Banking History conference held in Stockholm in 2002